Deformation behavior of β titanium alloy tubes in die-less forming with taper shape control - Takuma Kishimoto; Shunsuke Nozawa; Tsuyoshi Furushima (Journal of Materials Research and Technology, 2023)
The distributions of the outer and inner radii of die-less drawn β titanium alloy tubes were evaluated in the drawing direction to clarify the effect of the deformation behavior of the tube on taper shape control in the die-less forming. Ti–22V–4Al DAT51 (β Ti alloy) tubes with an outer radius of 0.81 mm were die-less drawn under various heating temperature and taper slope conditions. The outer and inner radius distributions were measured, and the drawing stress was evaluated during the drawing. As a result, a maximum reduction in cross-sectional area of 81% was achieved in a single pass of the die-less forming under a heating temperature of 800 °C and taper slope of −0.005. The outer radius became larger than that with the linear contour theory, which achieved the desired taper slope when the outer radius became smaller than a certain value during drawing. This is because the large slope in the deformation zone caused non-uniaxial tensile deformation dominated by wall thickness reduction. Therefore, the length between the heating and cooling coils should be large such that the slope of the deformation zone becomes small to satisfy uniaxial deformation, which is an assumption of the linear contour theory.